Optimisation of philanthropic waqf: the need for Maqasid-based legislative strategies - Mahmud , Mek Wok; Haneef, Sayed Sikandar Shah (LexisNexis, 2010)
Waqaf institution was most central in financing socio-religious and public welfare systems during the early days of Islam. More importantly, the contribution of philanthropic endowment(waqf khayri) substantially financed and sustained the social welfare institutions in Muslim societies. Gradually, however, the creation of this type of waqf dwindled and degenerated. Today, by and large, the waqf consists of religious kind particularly in Malaysia. To remedy this situation, we believe that we do not only need to rethink of the regulatory cum institutional structures of waqf but also have to seriously earmark jurisprudential strategies for the revival of waq khayri in this direction.